2021
DOI: 10.1164/rccm.202101-0136oc
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution and Susceptibility to Tuberculosis Infection in Urban Vietnamese Children

Abstract: Rationale: The Southeast Asian tuberculosis burden is high, and it remains unclear if urban indoor air pollution in this setting is exacerbating the epidemic.Objectives: To determine the associations of latent tuberculosis with common urban indoor air pollution sources (secondhand smoke, indoor motorcycle emissions, and cooking) in Southeast Asia. Methods:We enrolled child household contacts of patients with microbiologically confirmed active tuberculosis in Vietnam, from July 2017 to December 2019. We tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Our recent prospective cohort study in Vietnam analyzed the effect of indoor motorcycle storage and risk of TB infection. Parking multiple motorcycles inside the living area was associated with increased TB infection (aRR = 3.53, 95% CI, 1.12–11.1) [28 ▪ ]. A population-based case–control study in Nepal did not find significantly increased risk of TB infections among participants who used wood cookstoves compared with LPG (RR = 1.13, 95% CI, 0.73–1.77) [43].…”
Section: Epidemiologymentioning
confidence: 93%
See 1 more Smart Citation
“…Our recent prospective cohort study in Vietnam analyzed the effect of indoor motorcycle storage and risk of TB infection. Parking multiple motorcycles inside the living area was associated with increased TB infection (aRR = 3.53, 95% CI, 1.12–11.1) [28 ▪ ]. A population-based case–control study in Nepal did not find significantly increased risk of TB infections among participants who used wood cookstoves compared with LPG (RR = 1.13, 95% CI, 0.73–1.77) [43].…”
Section: Epidemiologymentioning
confidence: 93%
“…We performed a prospective cohort study in Vietnam, enrolling 109 children recently exposed to a household member with active TB. For each addition household smoker, children experienced a 2.56-fold increased odds of TB infection (aOR = 2.56, 95% CI, 1.27–5.16), with odds highest among children less than 5 years of age and children exposed to indoor smokers [28 ▪ ]. Smoking rates are elevated in TB endemic settings: For instance, in five high TB burden countries of India, China, Indonesia, the Philippines, and Pakistan, the Global Adult Tobacco Survey recently found elevated smoking rates in the adult population of 29, 29, 35, 24, and 20%, respectively [29].…”
Section: Epidemiologymentioning
confidence: 99%
“…A recent study showed associations between indoor air pollution and susceptibility to tuberculosis infection [ 45 ]. Briefly, higher levels of indoor air pollution exposure were shown to increase the odds ratio of latent tuberculosis infection in a cohort of 107 children living with 71 patients with active tuberculosis [ 45 ].…”
Section: Air Pollution and Infectious Lung Diseasementioning
confidence: 99%
“…A recent study showed associations between indoor air pollution and susceptibility to tuberculosis infection [ 45 ]. Briefly, higher levels of indoor air pollution exposure were shown to increase the odds ratio of latent tuberculosis infection in a cohort of 107 children living with 71 patients with active tuberculosis [ 45 ]. Based on these results, further studies regarding the associations of pollution with transmission risk of transmittable diseases, such as tuberculosis, and evaluation of the underlying mechanisms are required.…”
Section: Air Pollution and Infectious Lung Diseasementioning
confidence: 99%
“…11 Here, Blount and colleagues present the results of a cross-sectional study examining associations between multiple urban environmental exposures and latent tuberculosis infection among 109 child household contacts of 72 patients with active tuberculosis in Hanoi, Vietnam. 12 Key indoor air pollution exposure variables were assessed by questionnaire and were complemented by measurement of personal exposures to PM 2.5 over 48-72 hours. The authors constructed a multiple variable logistic regression model to explore the associations between these exposures and the outcome of latent tuberculosis infection, as defined by a positive tuberculin skin test.…”
mentioning
confidence: 99%